Pharmacogenetics of Antidepressants: Overview of Dosing Strategies in Major Depressive Disorder - Said, Saja; Özbey, Gül (Current Research in Pharmacy and Pharmaceutical Sciences II-2024, 2024)
Major depressive disorder is one of the most common psychiatric illnesses worldwide and has low recovery rates. Clinical evidence has suggested that individualized treatment based on pharmacogenetic data in antidepressant users may increase treatment success. Therefore, in this chapter, we focused on the effects of genetic variations in terms of therapeutic response and dose modifications on major depressive disorder patients using selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, tricyclic antidepressants, and monoamine oxidase inhibitors.